Methylenetetrahydrofolate reductase (MTHFR) polymorphisms and promoter methylation in cervical oncogenic lesions and cancer. Issue 4 (28th February 2013) - Botezatu, Anca; Socolov, Demetra; Iancu, Iulia V; Huica, Irina; Plesa, Adriana; Ungureanu, Carmen; Anton, Gabriela
Abstract The aim of this study was to investigate the role of methylenetetrahydrofolate reductase (MTHFR) polymorphisms and MTHFR methylation pattern in cervical lesions development among women from Romania, a country with high prevalence of human papillomavirus (HPV) cervical infections. To achieve this goal, blood samples and cervical cytology specimens (n = 77)/tumour tissue specimens (n = 23) were investigated. As control, blood and negative cytological smears (n = 50) were used. A statistically significant association was found between T allele of C677T polymorphism and cervical lesions, heterozygote women presenting a threefold increased risk (normal/cervical lesions and tumours: wild homozygote 34/41 (0.68/0.41), heterozygote 14/51 (0.28/0.51), mutant homozygote 2/8 (0.04/0.08); OR = 3.081, P = 0.0035). Using χ square test for the control group, the HPV‐negative and HPV‐positive patients with cervix lesions, a significant correlation between viral infection and T allele of C677T polymorphism (P = 0.0287) was found. The MTHFR promoter was methylated in all HGSIL and tumour samples, significant differences being noted between HPV‐positive samples, control group and cases of cervical dysplastic lesions without HPV DNA (P < 0. 0001) and between samples from patients with high‐risk (hr)HPV versus low‐risk (lr)HPV (P = 0.0026). No correlations between polymorphisms and methylation were observed. In Romania, individuals carrying T allele are susceptible for cervical lesions. MTHFR promoter methylation is associated with cervical severity lesions and with hrHPV.